It's Now or Never: Fertility-Related Knowledge, Decision-Making Preferences, and Treatment Intentions in Young Women With Breast Cancer—An Australian Fertility Decision Aid Collaborative Group Study - Peate, Michelle; Meiser, Bettina; Friedlander, Michael; Zorbas, Helen; Rovelli, Susan; Sansom-Daly, Ursula; Sangster, Jennifer; Hadzi-Pavlovic, Dusan; Hickey, Martha (Journal of clinical oncology, 2011)
For many young women with early breast cancer, fertility is a priority. Interventions to retain fertility options generally need to be accessed before chemotherapy, but many women do not receive information regarding these options in a timely fashion. Knowledge about fertility and decisional conflict has not previously been measured in young patients with breast cancer considering future pregnancies. One hundred eleven young women with early breast cancer who had not yet completed their families were recruited around the time of diagnosis. Knowledge regarding fertility-related information, decisional conflict, and preferences regarding fertility information and decision making was measured. From a potential fertility-related knowledge score of 10, the mean was 5.2 (standard deviation = 2.3; range, 0 to 10). Decreased knowledge was associated with increased decisional conflict about pursuing fertility preserving interventions (odds ratio [OR] = 0.57; 95% CI, 0.44 to 0.73; P < .001). Thirty-one percent of women reported that they would consider undertaking in vitro fertilization (IVF) as a method to conserve their fertility, whereas 38% were uncertain. Consideration of IVF was not related to whether subjects were in a committed relationship (OR = 1.20; P = .716) or a definite desire for more children (OR = 1.54; P = .513). Around diagnosis, many young patients with breast cancer have low levels of knowledge about fertility issues. Further, low knowledge is associated with increased decisional conflict, which is likely to undermine the quality of decision making. These findings suggest that targeted and timely fertility information may reduce decisional conflict and increase informed choice. Neither relationship status nor firm plans regarding future children reliably predict desire to pursue fertility preservation.